1991
DOI: 10.1111/j.1365-2621.1991.tb04788.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Flavor Compounds by Low Density Polyethylene Film

Abstract: The interactions of aldehydes, methyl ketones, methyl esters, sulfur compounds and alkylpyrazines with low density polyethylene (LDPE) were investigated. LDPE film, suspended on a stainless steel support, was immersed in simulated milk ultrafiltrate containing a flavor compound. After shaking the glass bottles containing the solutions and film samples for 24 hr at room temperature (24-+2"C), the flavor compound was extracted from both the LDPE samples and the SMUF, and quantitated using gas chromatography. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 6 publications
1
24
0
2
Order By: Relevance
“…The above-mentioned studies have demonstrated that polar volatile compounds such as benzaldehyde, citral, linalool, are absorbed much less to PE if compared with limonene or other non-polar hydrocarbon based volatiles, according to the rule ''like dissolves like''. Similarly, Shimoda et al (1988), Arora, Hansen, and Armagost (1991) and Charara et al (1992) have demonstrated that sorption into non-polar plastic materials such as polyolefines, increases with hydrophobicity of the longer chain flavor compounds. Ethyloctanoate is less polar than linalool, as it was shown by Eggers, Kenefick, Richardson, Wigglesworth, and Girard (2003) who based this statement on differences in Henry's constants (K H ): the higher the K H value, the lower the polarity of the molecule.…”
Section: Resultsmentioning
confidence: 95%
“…The above-mentioned studies have demonstrated that polar volatile compounds such as benzaldehyde, citral, linalool, are absorbed much less to PE if compared with limonene or other non-polar hydrocarbon based volatiles, according to the rule ''like dissolves like''. Similarly, Shimoda et al (1988), Arora, Hansen, and Armagost (1991) and Charara et al (1992) have demonstrated that sorption into non-polar plastic materials such as polyolefines, increases with hydrophobicity of the longer chain flavor compounds. Ethyloctanoate is less polar than linalool, as it was shown by Eggers, Kenefick, Richardson, Wigglesworth, and Girard (2003) who based this statement on differences in Henry's constants (K H ): the higher the K H value, the lower the polarity of the molecule.…”
Section: Resultsmentioning
confidence: 95%
“…O principal problema para o aproveitamento de reciclados na fabricação de embalagens para contato com alimentos relaciona-se à capacidade do material polimérico em absorver compostos químicos. 9,10 Estes compostos podem ser originados dos alimentos acondicionados, como por exemplo, componentes de sucos de frutas como laranja e maçã, [9][10][11][12] dos adesivos (polietileno e cola) usados como rótulo, das más condições de armazenagem da embalagem pós-consumo (contaminação por óleos, graxas, resíduos orgânicos e do próprio solo) e do mau uso da embalagem pelo consumidor antes do descarte (gasolina, defensivos agrícolas, inseticidas e raticidas, detergentes, desinfetantes e desodorizantes). 13 Todos esses compostos têm sido relatados como contaminantes, especialmente em embalagens PET (politereftalato de etila) pós-consumo.…”
Section: Contaminação De Alimentos Por Embalagens Plásticasunclassified
“…Better understanding is needed for those factors that influence the transport mechanism through polymer materials. The sorption of flavor compounds by polymer materials has been reported by several researchers, for a wide range of flavor compounds and materials (Arora et al, 1991;Imai et al, 1990;Halek and Meyers, 1989).…”
Section: Introductionmentioning
confidence: 96%